Study on the correlation between color and taste of beauty tea infusion and the pivotal contributing compounds based on UV–visible spectroscopy, taste equivalent quantification and metabolite analysis - Shan Jin; Mingjin Li; Ziqiong Liu; Ruihua Liu; Yuanchao Li; Yanyu Zhu; Yuwei Yuan; Pengchun Li; Pengming Li; Chunmei Chen; Yun Sun (Food Chemistry: X, 2024)
This study utilized a colorimeter to determine the color values of 23 beauty tea (BT) samples, the color and the taste characteristics were also quantitatively described through ultraviolet–visible (UV–Vis) spectroscopy and taste equivalent quantification. Furthermore, metabolomic analysis was conducted by using ultra-high-performance liquid chromatography-mass spectrometry (UPLC-MS). Correlation analysis was employed to preliminarily identify the compounds that contribute to the color and taste of BT infusion. Finally, the contributing compounds were further determined through verification experiment. The results showed that within a certain range, as the color of BT infusion deepened, the taste became stronger, more bitter and astringent, while on the contrary, it became sweeter and mellower. Theaflavins, kaempferol, astragalin, and 5-p-coumaroylquinic acid influenced both the color and taste of the BT infusion. Gallic acid was also determined as a contributor to the color. This study provides new insights into research on tea quality in infusion color and taste aspects.